Acute stress disorder and C-reactive protein in patients with acute myocardial infarction. (29th August 2020) - Bielas, Hannes; Meister-Langraf, Rebecca E; Schmid, Jean-Paul; Barth, Jürgen; Znoj, Hansjörg; Schnyder, Ulrich; Princip, Mary; von Känel, Roland
Abstract: Background: Myocardial infarction-triggered acute stress disorder (ASD) and subclinical inflammation associate with the development of posttraumatic stress disorder, and worsen the prognosis of myocardial infarction patients. We examined the relationship between ASD severity and C-reactive protein levels in patients with acute myocardial infarction. Methods: We assessed 190 patients (median age 59 years; 83% men) with a verified myocardial infarction within 48 h of an acute coronary intervention. Circulating levels of C-reactive protein were categorized according to their prognostic risk for cardiovascular disease: 0 to <5, 5 to <10, 10 to <20, and ≥ 20 mg/l. Patients completed the ASD-Scale (ASDS) for myocardial infarction-triggered symptoms and questionnaires for demographic factors, health behaviours, cardiac-related variables and psychosocial characteristics. Results: The ASDS sum score was positively associated with C-reactive protein categories in the bivariate analysis ( r  = 0.20, p  < 0.01). Significant relationships with C-reactive protein also emerged for dissociation ( r  = 0.25, p  < 0.001) and avoidance ( r  = 0.19, p  < 0.01), but not for arousal and re-experiencing. Similarly, C-reactive protein levels ≥ 20 mg/l versus < 20 mg/l were predicted by the ASDS sum score, and the dissociation, avoidance and arousal subscores (all p -values < 0.05) in the fully adjusted binary regression analyses. C-reactive protein levels ≥ 20 mg/l were also independently predicted by male gender, body mass index, lower education, and lower left ventricular ejection fraction and higher white blood cell count. Conclusions: Higher levels of myocardial infarction-triggered ASD symptoms associate with a greater inflammatory response in patients with acute myocardial infarction independently of important covariates. The findings suggest a link between myocardial infarction-triggered ASD symptoms and a heightened acute phase response with a potential impact on cardiovascular disease prognosis.